2011
DOI: 10.1007/s10096-011-1386-8
|View full text |Cite
|
Sign up to set email alerts
|

Clonality behind the increase of multidrug-resistance among non-invasive pneumococci in Southern Finland

Abstract: Multidrug-resistance among Streptococcus pneumoniae isolates, especially of serotype 19A, has increased in several countries recently. Even before the introduction of the pneumococcal conjugate vaccine into the Finnish National Vaccination Programme, the proportion of multidrug-resistant (MDR) pneumococci had doubled from 2007 to 2008, when it reached 3.6% in Southern Finland. Our aim was to look for a possible association between antimicrobial susceptibility and clonality among the MDR isolates. Twelve non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…A considerable increase in the disease caused by serotype 19A has been recorded after the introduction of PCV7 in some countries [24,26]. Of note, MDR serotype 19A isolates have also been identified in Israel and Finland before the large-scale use of conjugate vaccines as was the case in our study [27,28]. …”
Section: Discussionsupporting
confidence: 69%
“…A considerable increase in the disease caused by serotype 19A has been recorded after the introduction of PCV7 in some countries [24,26]. Of note, MDR serotype 19A isolates have also been identified in Israel and Finland before the large-scale use of conjugate vaccines as was the case in our study [27,28]. …”
Section: Discussionsupporting
confidence: 69%
“…Many studies have revealed that worldwide pneumococcal diseases are mostly caused by a few multidrug-resistant clones [ 11 , 12 , 13 , 14 ]. The aim of this study was to seek for the clonality among the pneumococcal strains detected in preschool children with recurrent upper respiratory tract infections (URTIs), based on the analysis of serotypes, antimicrobial susceptibility patterns and genotypic characteristics, including the transposons with resistance genes and clonality of the pneumococcal isolates performed by multilocus sequence typing (MLST) method.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, the World Health Organization (WHO) estimated that 0.7–1 million children, mostly from developing countries, died of pneumococcal disease annually [1]. The increasing trend of S.pneumoniae antimicrobial-resistance and emergence of multidrug- resistant (MDR) S.pneumoniae isolates, which may result from inappropriate use of antibiotics, has been a worldwide concern [2], [3], [4], [5]. The situation has been especially problematic in many Asian countries, China in particular.…”
Section: Introductionmentioning
confidence: 99%